Boycott! : the Movement for the Academic Boycott of Israel. - Maira, Sunaina (American Studies Now: Critical Histories of the Present Ser., 2017)
This title is part of American Studies Now and available as an e-book first. Visit ucpress.edu/go/americanstudiesnow to learn more. The Boycott, Divestment, and Sanctions movement (BDS) has expanded rapidly though controversially in the US in the last five years. The academic boycott of Israeli academic institutions is a key component of that movement. What is this boycott? Why does it make sense? And why is this an American Studies issue? These key questions and others are answered in this essential short book. Boycott! situates the academic boycott in the broader history of boycotts in the U.